Efectos económicos de la pandemia covid 19, en los principales fondos de pensiones privados de Colombia. (2022)
The returns of the portfolios offered by the Colombian PFAs during the period 2020 - 2021, corresponding to the years where the markets were hard hit by the COVID-19 pandemic, using 2019 as the base year and VAR model was performed using the average returns of the different funds jointly to analyze the impacts that the funds would have in relation to the total return of the funds, the results indicate that: (i) the returns of the different funds recovered a few months after their fall maintaining an economic rationality where the one with the lowest risk has the shortest recovery time and the lowest total fall; (ii) the fund that may have the greatest impact on the total profitability of the PFAs corresponds to the moderate fund as it is the one with the highest percentage of participation in the portfolios and likewise presents the best conditions to face instabilities and falls in the markets.